Perbandingan Analisis Distribusi Void Dan Pergerakan Agregat Terhadap Pemadatan Antara Campuran Fresh Aggregate Dan Rap Bergradasi Fuller - Setyowati, Erlin; , Ir. Sunarjono, M.T., Ph.D (2017)
Road is an important means for humans living in a country. The repair of the damage of road can be done with recycling technology to overcome the environmental problems. RAP (Reclaimed asphalt pavement) is a recycling material which does not have enough density, so that a study of solidity is needed, for example, the aggregate movements and void distribution. The goal of this study is to compare the mixture of RAP with the new mixture of aggregate in which both are regradated using the Fuller formula to view the movements of the aggregate and the distribution of void in the process of solidifying with the Marshall Hammer. The method of this study is done by giving agent stone as the reference to see the movements of aggregate and void distribution by measuring the quality of VIM (Void in Mix) intactly and cutting through each layer of those two mixtures. This study uses the cold mixture and the asphalt emulsion. In the observation of the aggregate movements, the tested object is cut vertically and horizontally to see the movements of agvregate in every layer. In the study of void distribution, the tested object is analyzed with two two ways, in which the tested object in total and it is cut in two parts to analyze the quality of VIM. Based on the result of this study, the movements of aggregate in the new mixture is more unhampered compared to the mixture of RAP (Reclaimed asphalt pavement) in both vertically and horizontally cuttings. In the result of void distribution testing, the new mixture of aggregate has smaller quality of VIM and the hollow distribution is more to spread. This shows that the fresh aggregate mixture has better solidity compared to the mixture of RAP viewed from the aggregate movements and the distribution of void.